2013
DOI: 10.1086/670624
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Intervention to Reduce Urinary Catheter Use and Associated Infection at a Veterans Affairs Medical Center

Abstract: We assessed the impact of a quality improvement intervention to reduce urinary catheter use and associated urinary tract infections (UTIs) at a single hospital. After implementation, UTIs were reduced by 39% ([Formula: see text]). Additionally, we observed a slight decrease in catheter use and the number of catheters without an appropriate indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Initial results, evaluated through June 2012, showed a 3.1% absolute reduction in indwelling urethral catheter prevalence hospital-wide, including a significant reduction in internal medicine units (4.6% absolute reduction; P = .01). 1 We also detected an 11.0% absolute reduction in inappropriate urethral catheter use. 1 The infection prevention literature is full of examples of interventions with initial success.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…Initial results, evaluated through June 2012, showed a 3.1% absolute reduction in indwelling urethral catheter prevalence hospital-wide, including a significant reduction in internal medicine units (4.6% absolute reduction; P = .01). 1 We also detected an 11.0% absolute reduction in inappropriate urethral catheter use. 1 The infection prevention literature is full of examples of interventions with initial success.…”
mentioning
confidence: 59%
“…1 We also detected an 11.0% absolute reduction in inappropriate urethral catheter use. 1 The infection prevention literature is full of examples of interventions with initial success. 2 Unfortunately, assessing sustainability, the extent to which program benefits (ie, effectiveness) persist, 3,4 is much less common; only a few studies have shown the long-term success of programs to reduce urethral catheter utilization or CAUTI.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, the device utilization ratio does not predict the proportion of appropriately used catheters, although a reduction over time is likely correlated with improvement. 39 Prior to implementation, evaluation of a proposed risk-adjusted device utilization metric with regard to usability as a quality metric and association with appropriateness is needed.…”
Section: Introductionmentioning
confidence: 99%